2020
DOI: 10.3390/app10217934
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Optical Laser System with Spatiotemporal Stabilization for Pump-Probe Experiments at SACLA

Abstract: We constructed a synchronized femtosecond optical laser system with spatiotemporal stabilization for pump-probe experiments at SPring-8 Angstrom Compact Free Electron Laser (SACLA). Stabilization of output power and pointing has been achieved with a small fluctuation level of a few percent by controlling conditions of temperature and air-flow in the optical paths. A feedback system using a balanced optical-microwave phase detector (BOMPD) has been successfully realized to reduce jitter down to 50 fs. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The need for only modest pulse energies results in the most compact, cost-efficient and least intensity-noisy near-infrared FEL pump-probe laser among the previously reported ones. [34][35][36] Only the OPCPA-based laser at LCLS shows comparable long-term pulse energy stability if it is driven with reduced pump power. [34] At full pump power, the LCLS system provides up to 90 W average power after the OPCPA, that is conversion of about 13.5 % of the power provided by the Yb:YAG amplifier.…”
Section: Discussionmentioning
confidence: 99%
“…The need for only modest pulse energies results in the most compact, cost-efficient and least intensity-noisy near-infrared FEL pump-probe laser among the previously reported ones. [34][35][36] Only the OPCPA-based laser at LCLS shows comparable long-term pulse energy stability if it is driven with reduced pump power. [34] At full pump power, the LCLS system provides up to 90 W average power after the OPCPA, that is conversion of about 13.5 % of the power provided by the Yb:YAG amplifier.…”
Section: Discussionmentioning
confidence: 99%
“…The same crystal was used to perform a cross-correlation and find a temporal overlap; the cross-correlation was fitted using the same methods described in . A temporal jitter between the optical and X-ray pulses was monitored using the SACLA timing tool system; however, recent upgrades to the synchronization of the optical laser and XFEL showed that the measured jitter measured was ≈50fs (FWHM) less than the instrument response of the measurement (≈100 fs), indicating that post-processing sorting of the TR-SFX data was unnecessary. The new system also actively corrects for slow timing drift between optical and XFEL beams, which was confirmed by cross-correlation measurements at the start and end of data collection (see SI for more details).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The 2D detector was a multi-port charge coupled device (MPCCD) having 512 × 1024 pixels 59 . Shot-to-shot variance in the X-FEL pulse arrival time is accounted for using an arrival timing monitor 60 . This jitter correction results in a temporal resolution approaching tens of femtoseconds 60 .…”
Section: Methodsmentioning
confidence: 99%